The importance of public policies to mitigate mental illness among public servants - Santana, Paulo Roberto Peixôto Lima de; Pinheiro, Alexandre Santos; Campos, Marilene de Souza (Seven Editora, 2024)
This study investigates the importance of public policies in mitigating mental illness in public servants, focusing on the implementation phase of the Public Policy Cycle. The research uses a systematic and quantitative approach, analyzing five articles that address different aspects of the theme. The analysis reveals a substantial understanding of the public policy cycle (76%), however, it highlights the need for further identification and detailing of challenges in implementation (48%). Regarding the effectiveness of the strategies (60%) and the allocation of resources (60%), a modest evaluation is observed, suggesting the importance of a more detailed analysis. The active involvement of civil servants in the implementation averages 60%, indicating a moderate consideration. These results highlight the complexity and importance of effective public policies for the mental health of civil servants. The discussion among the authors highlights the need to improve the analysis of specific challenges and to identify more effective strategies. In conclusion, the results provide valuable subsidies for the development of more effective public policies to promote the mental health of public servants. DOI:https://doi.org/10.56238/sevened2024.010-043